Pengaruh Store Atmosphere dan Kualitas Produk terhadap Kepuasan Pelanggan: (Studi pada Waroeng Kang Ujang di Korpri Bandar Lampung) - Suhartina; Onkky Ilham Umarudin Putra (Business Perspective Journal, 2022)
This study aims to explain the effect of Store Atmosphere (cleanliness, music, aroma, temperature) on customer satisfaction and the effect of product quality (service ability, reliability, and durability) on customer satisfaction. The researcher applied the survey method using a questionnaire as a research instrument in collecting data. Researchers also use the SPSS version 26 application with quantitative analysis which included validity and reliability test, classic assumption test, multiple linear regression analysis, coefficient of determination, hypothesis testing with F test and t test. Researchers chose respondents with a total of 30 people using purposive sampling method where the characteristics of the respondents have been determined by the researcher beforehand. The results show that the two independent variables, namely Store Atmosphere and Product Quality, both jointly and partially have a positive and significant effect on customer satisfaction. Product Quality variable is the most dominant variable in giving effect to Customer Satisfaction. Keywords: Store Atmosphere, Product Quality, Customer Satisfaction